The Impact of AI Transformation and Risks in Financial Services - Wau, Marselino; Laia, Firdaus; Wau, Ferdinand Tharorogo; Fau, Jhon Firman (Universitas Merdeka Malang, 2024)
This research presents a novel examination of the dual impacts of digital transformation and AI risks on the quality of financial services, with a particular focus on their interplay and the role of external regulatory factors. Unlike previous studies, this research offers a detailed quantitative analysis while integrating regulatory challenges and financial literacy as critical moderating factors. A survey of 84 respondents, including risk managers, IT managers, and executives from financial institutions, was conducted to analyze the specific effects of digital transformation and AI-related risks. The findings indicate that digital transformation negatively affects service quality, while AI risks positively impact operational efficiency and data analysis accuracy. However, these two variables explain only a small portion of the variance in service quality, suggesting that other factors, such as regulatory frameworks and financial literacy, play a significant role. The study recommends enhancing technological preparedness, implementing AI risk mitigation strategies, and addressing external factors to optimize service quality in the digital era.